Labor Mobility and Wage Dynamics: Understanding the Interplay of Factors in Modern Labor Economics - Yadin, Yadin; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Yendra, Yendra (Advances in Human Resource Management Research, 2024)
This qualitative research explores labor mobility and wage dynamics within contemporary labor economics. The study aims to provide a comprehensive understanding of the factors influencing labor market outcomes and inform evidence-based policymaking. The research methodology involves a systematic review of literature, employing established guidelines for transparency and rigor. Data collection entails identifying and retrieving scholarly articles, books, and reports from electronic databases, applying inclusion and exclusion criteria to ensure relevance and quality. Thematic analysis is employed to synthesize key findings, identify recurring themes, and develop a conceptual framework elucidating the relationships between labor mobility, wage dynamics, and related factors. The interpretation phase involves synthesizing and interpreting the analyzed data to develop coherent narratives and insights. The findings underscore the multifaceted nature of labor mobility and wage dynamics, highlighting the impact of economic, social, and institutional factors on individuals' access to economic opportunities and wage outcomes. Persistent barriers to mobility, including gender disparities and immigration policies, continue to limit access to economic opportunities for certain demographic groups. Additionally, technological advancements and institutional interventions play crucial roles in shaping wage dynamics and mitigating wage disparities. Interdisciplinary collaboration and evidence-based policymaking are essential for promoting inclusive and sustainable labor markets. This research contributes to advancing knowledge in the field of labor economics and informs strategies to foster economic opportunity for all individuals.